Autophagy or Apoptosis: Anticancer Molecular Mechanism of Epigallocatechin Gallate with Natural Polyphenol Effect on HepG2 Cells Viability - Rand R. Hafidh; Zahraa Q. Ali; Ahmed S. Abdulamir (College of Pharmacy University of Baghdad, 2023)
Background: The anticancer impact of Epigallocatechin gallate (EGCG) the highly active polyphenol of green tea was abundantly studied.  Though, the exact mechanism of its cytotoxicity is still under investigation. Objectives: Hence, the current study designed to investigate the molecular target of EGCG in HepG2 cells on thirteen autophagy- and/or apoptosis- related genes. Methods: The apoptosis detection analyses such as flow cytometry and dual apoptosis assay were used. The genes expression profile was explored by the real-time quantitative-PCR. Results: EGCG increases G0/G1 cell cycle arrest and the real-time apoptosis markers proteins leading to stimulate apoptosis in 70% of the treated HepG2 cells. The up-regulation was recorded in two of autophagy inhibitory genes (FOS-1, FOS-2) and apoptosis inducer gene (DDIT3). While the other ten genes expressed down-regulation after treatment. The down regulation was manifested in the genes of mitochondrial autophagy marker proteins (BNIP3, BNIP3L, and NBR1), the autophagy regulator genes (BIRC5, MAPK9), and the gene that implicated in protein biosynthesis and protein modification (ITGB1). The genes that have pro-apoptotic function in cells (CAPNS1, CFLAR, EIF4G, and RB1) were also showed down-regulation after treatment. Conclusion: Thus, the results demonstrated a potential effect of EGCG to induce apoptosis rather than autophagy in the treated HepG2 cells that could play a good target for therapy.